The 3D structure of human chromosomes in cell nuclei - Lukásová, E; Kozubek, S; Kozubek, M; Falk, M; Amrichová, J (Chromosome research, 2002)
The spatial arrangement of some genetic elements relative to chromosome territories and in parallel with the cell nucleus was investigated in human lymphocytes. The structure of the chromosome territories was studied in chromosomes containing regions (clusters) of highly expressed genes (HSA 9, 17) and those without such clusters (HSA 8, 13). In chromosomes containing highly expressed regions, the elements pertaining to these regions were found close to the centre of the nucleus on the inner sides of chromosome territories; those pertaining to regions with low expression were localized close to the nuclear membrane on the opposite sides of the territories. In chromosomes with generally low expression (HSA 8, 13), the elements investigated were found symmetrically distributed over the territories. Based on the investigations of the chromosome structure, the following conclusions are suggested: (1) Chromosome territories have a non-random internal 3D structure with defined average mutual positions between elements. For example, RARalpha, TP53 and Iso-q of HSA 17 are nearer to each other than they are to the HSA 17 centromere. (2) The structure of a chromosome territory reflects the number and chromosome location of clusters of highly expressed genes. (3) Chromosome territories behave to some extent as solid bodies: if the territory is found closer to the nuclear centre, the individual genetic elements of this chromosome are also found, on average, closer the centre of the nucleus. (4) The positions of centromeres are, on average, nearer to the fluorescence weight centre of the territory (FWCT) than to genes. (5) Active genes are not found near the centromeres of their own territory. A simple model of the structure of chromosome territory is proposed.
Keywords: Chromosomes, Human; lidské chromozomy, pár 17; Models, Genetic; buněčné jádro; modely genetické; metoda Monte Carlo; Nuclear Envelope; hybridizace in situ fluorescenční; geny; Computer Simulation; Heterochromatin; Lymphocytes; počítačové zpracování obrazu; Chromosomes, Human, Pair 17; počítačová simulace; Euchromatin; kompartmentace buňky; lymfocyty; Genes; heterochromatin; euchromatin; In Situ Hybridization, Fluorescence; jaderný obal; Cell Nucleus; ultrasonografie; Centromere; Humans; centromera; zobrazování trojrozměrné; lidské chromozomy; Cell Compartmentation; Imaging, Three-Dimensional; Image Processing, Computer-Assisted; Ultrasonography; lidé; Monte Carlo Method